Filosofia do amor em aforismos - Dax Moraes (O Que Nos Faz Pensar)
These following are a non-random, but also non-systematic exposition of a philosophy of Love in its grounding elements for a way of thinking about concrete human relationships in general. Each of the aphorisms starts from a perspective of love as having freedom by essence and also in its relations with the existencial experience of time. References can be found, here as quoted, there as mere inspiration.